2009
DOI: 10.1111/j.1440-1797.2009.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Drug‐induced anti‐neutrophil cytoplasmic antibody‐associated vasculitis

Abstract: SUMMARY:A recent development in the field of vasculitis is the increasing recognition that certain medications such as propylthiouracil can induce anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV). This review focuses on the data on causal drugs, possible pathogenesis, clinical description, diagnosis, treatment and prognosis of patients with drug-induced AAV. The pathogenesis of drug-induced AAV might be multifactorial. The clinical manifestations are similar to those of primary AAV, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 90 publications
(195 reference statements)
0
97
0
6
Order By: Relevance
“…4 Another well recognised cause is hydralazine. Vasculitis has also been documented with biologic therapies (eg tumour necrosis factor-targeted therapies) following their increasing use.…”
Section: Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Another well recognised cause is hydralazine. Vasculitis has also been documented with biologic therapies (eg tumour necrosis factor-targeted therapies) following their increasing use.…”
Section: Clinicalmentioning
confidence: 99%
“…The prognosis is good provided that the offending drug is withdrawn in time. 4 When faced with an acutely sick patient with signs consistent with either systemic infection or vasculitis, it can be difficult in the early stages to narrow the differential diagnosis. In some cases therefore, the combination of empirical immunosuppression and antibiotics can be justified pending further laboratory, imaging and histological information.…”
Section: Treatmentmentioning
confidence: 99%
“…Studies have shown that MPO-ANCA can be found in around 20 % of patients taking the drug and among these around 20 % develop vasculitic symptoms [46]. In most cases there are only mild skin lesions, but severe multi-organ failure may occur.…”
Section: Propylthiouracilmentioning
confidence: 99%
“…18 ANCA-associated vasculitis has been linked to various drugs, such as hydralazine, propylthiouracil, and minocycline. 19 Immunologic abnormalities found in drug-induced ANCAassociated vasculitis include high titer anti-MPO antibodies or combined positivity of both anti-MPO and anti-PR3, ANA, and anti-cardiolipin antibodies, similar to that observed in cocaine-levamisole cutaneous vasculopathy. 19 Typically, a prolonged exposure to a causative drug is required before the development of drug-induced autoantibody production.…”
mentioning
confidence: 99%